Good clinical practice guideline for the care of children with community-acquired pneumonia - Daylin Madruga Jiménez; Mercedes Fonseca Hernández; Orlando Morera Álvarez; Elizabeth Ríos Alverdi (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Community-acquired pneumonia is common in pediatric age. The objective of this work is to present a medical practice guideline, which helps addressing elements on diagnosis, epidemiology, etiology, risk factors, classification and management of children with community-acquired pneumonia. In the environment which is the context to this Guide, diagnosis and treatment, in most cases, is carried out in the primary care level, with a high incidence rate. Although very few patients require hospital care, the etiological diagnosis and the optimization of antibiotic treatment remain difficult challenges to overcome.